Eco-Epidemic Dynamics With Infected Communicable Infection From Prey to Predator: Effect of Recovery Delay for Predator - Rajawat, Richa; Dhar, Joydip; Sinha, Poonam (Communications in Mathematics and Applications, 2025)
In this paper, the system including communicable infection from prey to predator, represented by the growing rate of the prey as a healing of a predator’s, has been utilized to develop and analyze a four-dimensional, non-linear eco-epidemic model. In the context of the analysis, the exploration of all potential equilibrium points, along with an examination of their local stability conditions, has been conducted both with and without considering time delays. Additionally, the model’s positivity and boundedness have been confirmed. The positive and negative impact of the proposed model on the prey-predator population has been investigated aided by sensitivity analysis where the presence and validence of Bifurcation were elucidated by the numerical studies. The parameters were identified which explained the influence of disease and recovery delay over the model population. A right base for the perception of the behavioural effects of the prey-predator on eco-epidemiology has been prepared through the theoretical result. Based on the analytical result, numerical simulations were done so that the authenticity of the author’s numerical analytical approach using parameter values could be verified.